2023
DOI: 10.1007/s00265-023-03384-w
|View full text |Cite
|
Sign up to set email alerts
|

The effects of egg incubation temperature and parental cross on the swimming activity of juvenile brown trout Salmo trutta

Larry A. Greenberg,
Karl Filipsson,
Eva Bergman
et al.

Abstract: Personality varies among individuals and is influenced by the environment. Here, we tested the hypothesis that egg incubation temperature had carry-over effects on swimming activity of juvenile brown trout, Salmo trutta. Eggs from different crosses involving anadromous and lacustrine-adfluvial parents were incubated under two temperature regimes, unheated (cold) or heated c. 2.5 °C above ambient temperature (warm), until first exogenous feeding. In the laboratory, we used open-field tests to quantify swimming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 83 publications
1
7
1
Order By: Relevance
“…In this study, we showed that a temperature increase of 3°C during embryogenesis resulted in more active and aggressive brown trout fry. This result was the opposite of what we predicted, and it contrasts with those of Takatsu et al (2022) and Greenberg et al (2023). They found that increased temperature during egg incubation resulted in less distance moved by newly hatched brown trout fry in an open field test.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In this study, we showed that a temperature increase of 3°C during embryogenesis resulted in more active and aggressive brown trout fry. This result was the opposite of what we predicted, and it contrasts with those of Takatsu et al (2022) and Greenberg et al (2023). They found that increased temperature during egg incubation resulted in less distance moved by newly hatched brown trout fry in an open field test.…”
Section: Discussioncontrasting
confidence: 99%
“…They found that increased temperature during egg incubation resulted in less distance moved by newly hatched brown trout fry in an open field test. Effects on egg incubation temperature on distance moved in an open field test seem, however, to be ephemeral (Greenberg et al, 2023). We measured the proportion of time spent swimming as a measure of activity, and we did not use an empty container as our test arena (as is the case in an open field test).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As we no longer had these fish available to further explore the mechanism behind this difference in metabolic rates, we used brown trout from the same population raised at the same hatchery and under similar conditions in 2018-2019. These trout were used in several different studies, all focused on testing the effect of incubation temperature (2 temperatures) and parental cross (4 crosses) on the growth and behavior of juvenile fish [19][20][21]. In the study reported here, we limited ourselves to one cross, i.e., anadromous S. trutta, which were either incubated at ambient water (control) temperatures or at elevated temperatures (warm), approximately +2.7 • C above ambient water conditions [19][20][21].…”
Section: Rearing Of Fishmentioning
confidence: 99%